2022
DOI: 10.1088/1755-1315/1037/1/012055
|View full text |Cite
|
Sign up to set email alerts
|

Head-Cover vibration investigation of a Prototype Reversible Pump-Turbine Unit during Start-up in Pump mode. Part I: Fluid dynamic analysis

Abstract: Reversible pump-turbine units of pumped storage power stations can generate power in turbine mode and store electric energy in pump mode for load balancing of the electric power grid. During the start-up transient process in pump mode of a reversible pump-turbine, the flow pattern and the pressure distribution in the flow channel change dramatically with the increasing opening angle of guide vanes. The unsteady pressure of the flow passing channel can cause severe vibration on the head-cover, bottom ring, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…L = (Rcos α + rsin θ, Rcos α + rcos θ) (10) here c = ωr 2 0 . According to Helmholtz's theorems, vortex tubes demonstrate conservativity.…”
Section: Preliminary Analysis Of Fluid Kinematic Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…L = (Rcos α + rsin θ, Rcos α + rcos θ) (10) here c = ωr 2 0 . According to Helmholtz's theorems, vortex tubes demonstrate conservativity.…”
Section: Preliminary Analysis Of Fluid Kinematic Progressionmentioning
confidence: 99%
“…It was found that the influence of the clearance dominated the axial thrust much more than the influence of the runner blades. Yang et al investigated the transient characteristics of the internal flow of pump turbines during start-up and shutdown by numerical simulation [10], and further studied the influence of flow-induced vibration on the structural stress characteristics of non-rotating components [11].…”
Section: Introductionmentioning
confidence: 99%